Identification of Fungal secondary Metabolites of Isaria fumosorosea by GC-Mass Analysis used for the green synthesis of Silver nanoparticles - Maryem Akbal Hasoon; Ahmed Saeed Mohmed; Jamaal Hussein Kadhim (Kufa Journal for Agricultural Sciences)
Entomopathogenic fungi are considered one of the biological control agents for insects, which have a safe and environmentally friendly role. The work of insect-pathogenic fungi is not limited to their mechanism of action to produce spores. Still, it also secretes secondary metabolites, which also have a role in insect pathogens, and recently it has appeared to have a role in the biosynthesis of nanoparticles. Isaria fumosorosea is one of the most important Entomopathogenic fungi which secretes many secondary metabolites. The current study included the detection of secondary metabolites of I. fumosorosea by GC-Mass analysis and the possibility of using these metabolites as reducing agents in the synthesis of silver nanoparticles. our results revealed that the crude filtrate contains many compounds such as Sorbitol, Heptadecane, Z-5-Nonadecene, and Heneicosane through a GC-Mass analysis. The results also indicated that the secondary metabolites were successful in the biosynthesis of silver nanoparticles whose properties have been described by several methods such as UV-Vis spectrophotometer where The peak of recorded at 419 nm In addition to the use of the Field Emission Scanning Electron Microscope (FESEM) who explained the size and shape of Ag NPs where range size was 44.66 -89.23 nm with roughly circular or spherical in shape. Our study concluded that the crude filtrate of I. fumosorosea contains many secondary metabolites compounds which showed effectiveness in the biosynthesis of  Ag NPs.